Study on ICT Skills for Cloud Computing Implementation among Quantity Surveyors in Pre-Construction Stage - Mohd Zaini, Nur Liyana; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2022)
Cloud computing is a new paradigm of information technology (IT) that allows users to access software, hardware, and data stored on a cloud server. However, ICT adoption leads to a high-cost investment, a lack of knowledge, expertise, adequate training, etc. in adapting it to the construction industry. These problems affect the implementation of cloud computing in the construction industry. Thus, this study was conducted to identify the key ICT skills needed and then, to determine the challenges and the relationship between key ICT skills needed and challenges among QS at pre-construction. The research used a quantitative (questionnaire) method and the respondents of this research are the Quantity Surveyor at Johor. 200 questionnaires were distributed and 103 questionnaires were returned. Then, the data were analysed by using the SPSS to provide the frequency analysis, descriptive statistics, and correlation analysis. Key ICT skills are highly endorsed by the respondents and the results stated that cloud services require key ICT skills to be implemented effectively. Then, major challenges to implementing cloud computing at the pre-construction stage are the lack of knowledge and skill among employees, cost issues, and security issues. In addition, ICT-related and cloud computing challenges seemed to significantly affect the respondents’ needed key ICT skills in using the cloud computing technology. In conclusion, this research contributes to enhancing the understanding of the relationship between the ICT skills needed and the challenges to implementing cloud computing among the Quantity Surveyor at the pre-construction stage.